An Empirical Study of Online Social Influence Marketing with Reference to Customer’s Product Purchase Decision and Product Recommendation - Sharma, Monika; Kalra, Deepshika (Indian Journal of Marketing, 2011)
In recent times, people have started getting influenced by each other - online, in small groups, through peer pressure, reciprocity or flattery - which has given rise to a whole new form of marketing, called Social Influence Marketing (SIM). It is defined as marketing to the network of peers that surround and influence the customer across social platforms like different Social Media (Online & Offline). The rise of SIM has made us realize that the social Web and the mainstream Web are converging and that digital marketers need to deliver better value exchanges to consumers and allow for influence, more directly. Online social influence marketing is practiced using various online social media tools like consumer opinions posted online through blogs, recommendations done by known people or unknown people through online social networks such as ’Orkut’, ’Facebook’, ’Twitter’ etc. It also includes anonymous consumer reviews sites, branded web sites, online video advertisements (e.g. done though ’Youtube’) and online banner advertisements. This paper attempts to determine how much Online Social Influence marketing has been able to influence customer’s product purchase decision and whether customers really trust these online social media in terms of peer reviews and other influential sources, which makes them believe these online social media, in order to make a product purchase decision. A chi-square test has been carried to find out the association between customer’s purchase decision and the role Online Social Media has played in terms of influencing the customer and determining customer’s trust in Online Social Media. The researchers have also investigated whether customers further recommend products to other people using Online Social Media tools.